Autoradiographic investigation of effects of high-dose colchicine on dentinogenesis in rat incisors - Nogueira, T. O.; Zorn, T. M T; Stene, T.; Koppang, H. S. (Karger Publishers, 1988)
Twelve female Wistar rats received 1.5 mg/kg of colchicine (CLC) intravenously. Control animals were similarly injected with isotonic saline solution. The animals were killed 5 h, 24 h, 3 days and 7 days after injection. Ninety minutes prior to sacrifice, all animals received an intraperitoneal injection of 3H-proline. Autoradiograms of maxillary incisors showed that CLC increased the retention of the labeled precursor in the odontoblasts. It was also shown that the odontoblasts in the different sectors of the rat incisor present different sensitivities to the CLC action.
Keywords: colchicine; radioisotope; animal cell; animal experiment; dentin; incisor; intravenous drug administration; nonhuman; odontoblast; rat; tooth development; Animal; Autoradiography; Colchicine; Dentin; Dentinogenesis; Female; Incisor; Proline; Rats; Rats, Inbred Strains